Factors Affecting Properties of Cellular Lightweight Clay Improved with Fly Ash Geopolymer and Cement - Thumrongvut, Jaksada; Audomrak, Thanasak; Wonglakorn, Nattiya; Tabyang, Wisitsak; Tiyasangthong, Sermsak; Suksiripattanapong, Cherdsak (Civil Engineering Journal, 2025)
This research investigated the unit weight and unconfined compressive strength (UCS) of cellular lightweight high-calcium fly ash geopolymer and cement-stabilized soft Bangkok clay (CLFAG-OPC stabilized SC) as potential lightweight embankments and backfill materials. The investigated parameters included the soft clay:fly ash (SC:FA) ratio (50:50 to 90:10), ordinary Portland cement (OPC) content (0%-3%), water content (1.5LL-3.0LL), liquid alkaline content (L) (0.6FA to 1.5FA), NS:NH ratio (0.5-3), NH concentration (8 M), air foam content (Ac) (0%-150% by SC volume), and curing time (7-90 days). The results indicated that the SC:FA ratio, OPC content, water content, NS:NH ratio, L content, and Ac significantly influenced both the unit weight and UCS of samples. Increasing water content, L content, and Ac generally reduced unit weight, except when influenced by FA content, OPC content, and the NS:NH ratio. The optimal composition for maximum UCS was achieved with an SC:FA ratio of 50:50, OPC content of 3%, water content of 2.0LL, NS:NH ratio of 1, L content of 0.6FA, and 0% Ac. A predictive equation for unit weight was proposed using phase diagrams. Additionally, mix design charts were shown to be valuable tools for calculating the unit weight and UCS, demonstrating their effectiveness for lightweight embankment and backfill applications.